Difficulties of Quality Education in Higher Education in India - Raja, Piyush; Rahman, M. M. (Future Science / FSH-PH Publications, 2021)
Higher education will lead the world in 21st era because it not only creates greater personal and social prosperity, but it also affects all facets of development, including intellectual, social, cultural, aesthetic, physical, spiritual, and human capital development, directly or indirectly. Afterward, US and China, India has the world's third largest higher education system. University Grants Commission (UGC) is the largest regulatory body at the higher level, and it enforces its guidelines, advises the administration, and facilitates communication between the federal government and the states. The University Grants Commission oversees accreditation for higher education by 15 independent institutions. While the nation has progressed significantly in terms of enrolment, the standard of education continues to be a source of concern, which is critical for achieving the country's goals and implementing national policy. Weak facilities, exam-driven curriculum, memory-based exams, a shortage of qualified faculty, ineffective teaching strategies, a lack of funding, inconsistencies in government policy on higher education, entrenched political motives, massive demands from the youth population, political unrest, increasing privatisation, a lack of access and equity, and so on are some of the problems in higher education. There are several more problems like this, and this paper objectively examines all of them, as well as potential solutions.